Vitellogenin dynamics and reproductive morphology at sexual maturity of Philippine Mallard (Anas platyrhynchos domesticus L) fed with zinc supplemented diet - Arnolfo M. Monleon; Angel L. Lambio; Renato S. A. Vega; Severino S. Capitan; Carmelita M. Rebancos (Syiah Kuala University, 2012)
The vitellogenin (Vtg) is a precursor for the synthesis of egg yolk protein. Feeding with zinc-supplemented diet is hypothesized to increase the circulating Vtg thereby enhancing reproductive development. A total of 80 ducks,aged 16 weeks old, were randomly assigned to treatment groups; namely: group A with 40 ducks fed with 30 ppm zinc-supplemented diet (zinc positive) and group B with 40 ducks fed with no added zinc (zinc negative). Thecirculating Vtg at sexual maturity (155.11±10.83 days old) were determined from the blood sera. The sera were assayed for Vtg in duplicate using 96–well microplate and read the optical density at 415nm. The zinc concentrationof the samples was calculated using the nonlinear regression =OD = a x [Zn2+] / (b + [Zn2+]. Results show that the circulating Vtg in the blood sera of ducks at sexual maturity were 0.69±0.07 Gg Zn dL-1. The feeding of zinc-treateddiet had no significant influenced on the concentration of circulating Vtg. There was also insignificant difference in the reproductive morphology of ducks fed with or without added zinc. The Vtg concentration had no correlation withreproductive parameters but found to be positively correlated with liver weight (H=0.21) and negatively correlated with body weight (H = -0.24).